Strategi Pemasaran Produk UMKM Sambal Di Dusun Beciro Jumputrejo Melalui Pengembangan Distribusi Produk - Fatimatus Zahro; Zahrotul Jannah; Didit Darmawan; Jahroni Jahroni; Uswatun Chasanah; Utami Puji Lestari; Rahayu Mardikaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have a very important role in the Indonesian economy. This is in line with the service objectives that have been carried out to advance MSMEs in Beciro Hamlet. For example, in one of the MSMEs in Jumputrejo Village, namely Mother Vivi's chilli products. Based on the survey results, two service methods were found that can be applied to increase sales of Bunda Vivi's chilli products, namely direct interviews and literature studies related to the writing of this service journal. By applying these methods, the KKN 04 Group of Sunan Giri University Surabaya, East Java, was able to help improve the quality of sales by making logo stickers and creating a marketplace account on one of the e-commerce platforms, Shopee. Through this service, we managed to make a significant contribution by increasing the sales of Mother Vivi's sambel products by 100%.